Design and Build A Plastic Pellet Monitor System Prototype on An Injection Molding Plastic Storage Tank with The Blynk Application - Agus Dendi Rochendi; Irfan Kampono (Institute for Research on Innovation and Industrial System (IRIS), 2020)
Plastic injection molding machines, plastic pellet filling is generally done manually in a closed tank. Operators have difficulty seeing the level of plastic pellets in the storage tank, it disturbs work productivity. The research that was carried out was the prototype design of monitoring the volume of plastic pellets in the storage tank using the HC-SR04 ultrasonic sensor ESP8266 data processing equipped with LCD as well as data communication media. The plastic pellet tank monitor system can work properly as expected. The average accuracy of the ultrasonic sensor 1 is 97.2% and the average accuracy of the ultrasonic sensor 2 is 95.3%. Ultrasonic sensor readings in this study the minimum level is at 0 cm and the maximum level is 32.8 cm. It takes an average of 1.9 seconds from reaching the minimum limit until a notification appears on the Blynk application.